(untitled) (ENTHYMEMA, 2011)
This is the first Italian translation of Stanley Fish’s essay Why No One’s Afraid of Wolgang Iser, published on Diacritics, vol. 11, no. 1 (Spring 1981). The essay was written as a reply to Iser’s interview published in the previous number of Diacritics, but it especially takes the cue from one of the most important works by Iser, namely The Act of Reading: A Theory of Aesthetic Response, originally published in 1976. In this essay Fish criticizes and refutes many of the cornerstones of Iser’s theory, from the ontological nature of the agents involved in the act of reading to the phenomenological examination of the mechanics of interpretation, which Fish applies to the literary text as well as to the perception of the real world.